Study of jambolan pulp bioactive compounds / Estudo de compostos bioativos presentes na polpa de jambolão (Caderno de Ciências Agrárias, 2017)
Jambolan fruit is small and the taste, although a little astringent, is pleasant to the palate, especially when ripe; the color presents great visual impact, but with no characteristic aroma. It is an excellent source of antioxidants, thus could be included in the ranking of fruits with excellent nutraceutical potential. These natural compounds have aroused interest, due to their nutritional and therapeutic effects, due to their antioxidant action. The objective of this work was to characterize the jambolan fruit as to the bioactive compounds present in its pulp. Analyzes of total phenolic compounds, anthocyanins, tannins and, antioxidant capacity were carried out by the DPPH free radical scavenging method. The jambolan presented total phenolic compounds content of 309.03 mg GAE 100 mL-1 of pulp; anthocyanins of 220.87 mg L-1 of pulp, tannins of 16.82 mg TA 100 mL-1 of pulp, EC50 of 245.61 mg L-1 of pulp, and 96.03% of free radical sequestration. Jambolan is a fruit that has high antioxidant capacity and its processing in the form of jelly, sweets and beverages would be a way to add value to the fruit and provide a food with nutraceutical properties for the consumers.Resumo: O fruto jambolão é pequeno e o sabor, apesar de um pouco adstringente, é agradável ao paladar, especialmente quando maduro, a cor apresenta grande impacto visual, porém sem aroma característico forte. Excelente fonte de antioxidantes, pode ser incluído no ranking dos frutos com ótimo potencial nutracêutico. Estes compostos naturais têm despertado interesse, devido aos seus efeitos nutricionais e terapêuticos, pela ação antioxidante. O objetivo deste trabalho foi caracterizar o jambolão quanto aos compostos bioativos presentes em sua polpa. Foram realizadas as análises de compostos fenólicos totais, antocianinas, taninos e capacidade antioxidante, pelo método do sequestro de radicais livres do DPPH. O jambolão apresentou médias do teor de compostos fenólicos totais de 309.03 mg ác. gálico 100 mL-1 de polpa; antocianinas de 220.87 mg L-1 de polpa, taninos de 16.82 mg ác. tânico 100 mL-1 de polpa, EC50 de 245.61 mg L-1 de polpa e 96.03% de sequestro de radicais livres. O jambolão é uma fruta que apresenta alta capacidade antioxidante e o seu processamento em forma de geleia, doces e bebidas seria uma maneira de agregar valor à fruta e propiciar um alimento com propriedades nutracêuticas para o consumidor.